Chasing rabies herd immunity: evaluating dog vaccination strategies and post-vaccination survey reliability in urban and peri-urban Bangladesh - Swedberg, Catherine; Siddiqi, Umme Ruman; Keshavamurthy, Ravikiran; Rana, Md Sohel; Islam, Kamrul; Kennedy, Erin; Ross, Yasmeen B.; Bonaparte, Sarah; Lohr, Frederic; Mursalin, Hasan Sayedul; Kamruzzaman, Md; Gamble, Luke; et al. (Frontiers in Microbiology, 2026)
IntroductionMass dog vaccination (MDV) is essential for eliminating dog-mediated rabies, responsible for over 95% of the estimated 74,000 annual human rabies deaths. Achieving ≥ 70% vaccination coverage necessary for herd immunity remains challenging, underscoring the need for effective vaccination strategies and reliable post-vaccination evaluation methods.MethodsMDV campaigns were conducted in four site in Bangladesh (two urban, two peri-urban) using three strategies: standard capture-vaccinate-release (CVR), enhanced CVR (eCVR), and roaming static point (RSP). Post-vaccination sight re-sight (SRS) and household surveys were used to characterize dog populations and estimate coverage. Three enumeration methods were compared to assess reliability and utility for campaign evaluation.ResultsOver 12 working days, 9,195 dogs were vaccinated. eCVR achieved the highest operational efficiency (40.2 dogs/vaccinator/day), followed by standard CVR (36.6) and RSP (18.2). Post-vaccination surveys indicated that over 93% of dogs were free-roaming, and around 30% were unowned, highlighting limitations of static point strategies. Human-to-dog ratios (HDRs) were lower than the 100:1 planning estimate and varied widely across sites (mean: 67.8; range: 21.1–129.6), with no significant difference between urban and peri-urban areas (p = 0.479). Coverage estimates differed by enumeration method: 19% (dog density), 32% (HDR), and 47% (SRS), with comparable SRS- and HDR-based estimates (p = 0.920), and dog density formula estimates significantly lower (p = 0.014). Averaging across enumeration methods and sites, eCVR achieved the highest coverage (45%), followed by standard CVR (37%) and RSP (16%), with estimated RSP coverage significantly lower than eCVR (p = 0.028).DiscussionThe wide heterogeneity in HDRs highlights the limitations of using a single ratio for national dog population extrapolation. Effective rabies control requires locally tailored vaccination strategies, real-time monitoring, and robust enumeration techniques to guide planning and ensure reliable evaluation of campaign impact.